YOUTUBE SUBSCRIPTION, GEOGRAPHICAL RESIDENCE AND ACCENT ALTERATION (A Case Study of an English-Indonesian Bilingual Child) - Septhia Irnanda; Kismullah Abdul Muthalib; Yulsafli Yulsafli; Asriani Asriani (UICELL, 2022)
This study investigates the changes in English vowel production in a 10-year-old bilingual child residing in Aceh Indonesia. The subject speaks English (the subject acquired British English since toddler) predominantly at home and Indonesian at school. She has been watching videos of American-English Youtubers on daily basis for approximately four years. The absence of British English exposure due to the subject’s geographical change from Bristol to Indonesia, combined with the increasing virtual contact with American English from the internet has altered the subject’s English oral production phonologically. This study aimed to explore the areas of phonology affected, how and why it happened; whether the change occurred naturally, or intentionally and if the identity played an important role in the alteration. This is a descriptive-quantitative study using two sources of data; primary and secondary. The primary data was retracted from an in-depth interview with the subject, whilst the secondary data was the subject’s English production taken from the subject’s parents' video collection. Taken together, the findings show that phoneme is the only phonological level affected by the new language situation and exposure, while the prosodic area is maintained. In addition, the reason for this accent change is natural instead of intentional. The subject confesses that she was unaware of the change and thinks she needs not to alter her English accent because she rarely uses the language for social purposes. The findings suggest that language daily virtual exposure like YouTube channels can change one’s language, phonologically even without the subject's residential area being put into consideration. Keywords: accent-change, phonology, pronunciation, YouTube, bilingualism, multilingualism